2010
DOI: 10.1083/jcb.201001048
|View full text |Cite
|
Sign up to set email alerts
|

The NuRD chromatin–remodeling complex regulates signaling and repair of DNA damage

Abstract: NuRD is recruited to DNA double-strand breaks, where it promotes RNF8/RNF168 histone ubiquitylation and accumulation of DNA repair factors (see also related paper by Larsen et al. in this issue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
247
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(260 citation statements)
references
References 46 publications
13
247
0
Order By: Relevance
“…Recent studies have shown the importance of CHD4 in response to ionizing radiation and PARP inhibitors [29][30][31][32]38]. In this study, we demonstrated that CHD4 plays a role in the resistance to epirubicin, which induces DSBs in cancer cells.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies have shown the importance of CHD4 in response to ionizing radiation and PARP inhibitors [29][30][31][32]38]. In this study, we demonstrated that CHD4 plays a role in the resistance to epirubicin, which induces DSBs in cancer cells.…”
Section: Discussionsupporting
confidence: 58%
“…Other repressive complexes, such as NuRD and histone deacetylases (HDACs) (43)(44)(45)(46), also transiently accumulate at DSBs, supporting this idea. The formation of repressive structures at DSBs in open chromatin has parallels with DSB repair in heterochromatin.…”
Section: Discussionsupporting
confidence: 50%
“…DSB repair in heterochromatin requires the ATM-dependent phosphorylation of kap-1 (30,31), which releases the repressive CHD3 chromatin remodeler (47) and promotes chromatin relaxation and facilitates DSB repair (31,32,47). Thus, immediately after DNA damage, both euchromatin and heterochromatin domains have similar structural organization, including high density of H3K9me3 and the presence of repressive complexes, such as kap-1, HP1α, methyltransferases, HDACs, and CHD3/CHD4 remodeling ATPases (31,32,(43)(44)(45)(46)(47). This rapid, but temporary, formation of repressive chromatin may inhibit local transcription, compact the local chromatin structure, and rewrite the local epigenetic landscape, stabilizing open chromatin structures and limiting DSB mobility during the initial moments following DSB production.…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair is no exception, and dynamic changes in chromatin condensation and accompanying histone marks have been recognized as inevitable DDR pathways [15,[75][76][77][78][79][80]. Here, too, the DDR relies on recruitment of existing players in the chromatin organization arena [32][33][34][75][76][77][78][79][81][82][83][84][85]. H2B monoubiquitylation was previously implicated in the DDR in the budding yeast [86][87][88].…”
Section: Rnf20-rnf40 Is Called To Emergency Action Upon Dna Damage Inmentioning
confidence: 99%